Decolonialidade e confluência na educação quilombola : experiências no ensino de literatura e na oralitura - Dias, Plínio Rogenes de França (2024)
This thesis is the result of an action research at the Quilombola Municipal School of Early Childhood Education and Elementary Education Professor Antônia do Socorro Silva Machado, institution located in the quilombola territory of Paratibe, located in Paratibe neighborhood, southern outskirts of the municipality of João Pessoa-PB. The qualification of the school as quilombola made emerging the decolonial studies applied to the curriculum in addition to reinforcing researches that are already consolidated in academia regarding on: quilombism; anti-racist didactics; implementation of laws 10639/03 and 11645/08; decoloniality in education. The crossing of these themes provided a collection of data and diversified theoretical contributions in the areas of popular education; education for ethnic-racial relations; cultural studies and Africanities; orality and literature teaching. The description of the field, using ethnographic methodology, determined important themes for the literary reading work, such as issues linked to gender, territoriality, culture of peace, family, ancestry, religiosity and alimentation. Data were collected from field diaries, interviews, records of classroom experiences, culture circles and integrative practices. All subjects are students in the final years of elementary school, members of the quilombola community and the school. The research was authorized by the ethics committee of the Federal University of Paraíba and, for this reason, all records of speeches and images of people, especially minors, are preserved in accordance with the regulations for research with human beings. Initially, the field is presented and leads to debates on curriculum, decoloniality and quilombola education based on Afro-Brazilian civilizational values. The questions that were raised promoted a redefinition of teacher training to work in this type of teaching, especially regarding to orality and a repertoire of Afro-Brazilian readings. The search to fill these gaps also motivated a re-elaboration of knowledge in the field of teaching methodology for literary reading and actions regarding to oration, which proved to be an important category for the school’s quilombist project. Several teaching-learning experiences were developed inside and outside traditional pedagogical environments, expanding perceptions about territoriality, corporeity and rituality in the institution’s pedagogical praxis. The questions about curriculum, decoloniality and quilombola education were developed based on GOMES (2017; 2021), SANTOS (2023), RUFINO (2019; 2021), MALDONADO-TORRES (2020), NASCIMENTO (2019; 2022), PEREIRA (2007), HOOKS (2017; 2021), NOGUERA (2020; 2023) ARROYO (2013) e BRANDÃO (1984; 2006). For debates on orality, oraliture and teaching literary reading, we use ZUMTHOR (2000; 2010), ROTHENBERG (2006), BARTHES (2004), MARTINS (1997; 2021), PINHEIRO (2015; 2018), BAJOUR (2012), COSSON (2020) and LARROSA (2021) in addition to several nonacademic voices, such as poets, singers, quilombolas, indigenous people and religious leaders. Various practices were carried out with oral debates and oralization of poems and short narratives, highlighting readings by Conceição Evaristo, Cristiane Sobral, João Cabral de Melo Neto, Patativa do Assaré, Elisa Lucinda, Sônia Sultuane, Rubem Braga, in addition to several songs and texts by the professor-researcher himself.